Inkjet-Printed Dielectric Layer for the Enhancement of Electrowetting Display Devices - Hongwei Jiang; Rongzhen Qian; Tinghong Yang; Yuanyuan Guo; Dong Yuan; Biao Tang; Rui Zhou; Hui Li; Guofu Zhou (Nanomaterials, 2024)
Electrowetting with a dielectric layer is commonly preferred in practical applications. However, its potential is often limited by factors like the properties of the dielectric layer and its breakdown, along with the complexity of the deposition method. Fortunately, advancements in 3D inkjet printing offer a more adaptable solution for making patterned functional layers. In this study, we used a negative photoresist (HN-1901) to create a new dielectric layer for an electrowetting display on a 3-inch ITO glass using a Dimatix DMP-2580 inkjet printer. The resulting devices performed better due to their enhanced resistance to dielectric breakdown. We meticulously investigated the physical properties of the photoresist material and printer settings to achieve optimal printing. We also controlled the uniformity of the dielectric layer by adjusting ink drop spacing. Compared to traditional electrowetting display devices, those with inkjet-printed dielectric layers showed significantly fewer defects like bubbles and electrode corrosion. They maintained an outstanding response time and breakdown resistance, operating at an open voltage of 20 V. Remarkably, these devices achieved faster response times of ton 22.3 ms and toff 14.2 ms, surpassing the performance of the standard device.